Cloning and expression characterization of elongation of very long-chain fatty acids protein 6 (elovl6) with dietary fatty acids, ambient salinity and starvation stress in Scylla paramamosain - Lin, Zhideng; Wu, Zhouyu; Huang, Chaoyang; Lin, Huangbin; Zhang, Mingyao; Chen, Mingfeng; Han, Kunhuang; Huang, Weiqing; Ruan, Shaojiang (Frontiers in Physiology, 2023)
Introduction: Elongation of very long-chain fatty acids protein 6 (ELOVL6) played crucial roles in regulating energy expenditure and fatty acid metabolism. Many studies have performed to investigate the physiological roles and regulatory mechanisms of elovl6 in fish and animals, while few studies were reported in crustaceans. Methods: Here we reported on the molecular cloning, tissue distribution and expression profiles in response to dietary fatty acids, ambient salinity and starvation stress in Scylla paramamosain by using rapid amplification of cDNA ends (RACE) and quantitative real-time PCR. Results: Three elovl6 isoforms (named elovl6a, elovl6b and elovl6c) were isolated from S. paramamosain in the present study. The complete sequence of elovl6a was 1345 bp, the full-length sequence of elovl6b was 1419 bp, and the obtained elovl6c sequence was 1375 bp in full length. The elovl6a, elovl6b and elovl6c encoded 287, 329 and 301 amino acids respectively, and exhibited the typical structural features of ELOVL protein family members. Phylogenetic analysis showed that the ELOVL6a from S. paramamosain clustered most closely to ELOVL6 from Portunus trituberculatus and Eriocheir sinensis, while the ELOVL6b and ELOVL6c from S. paramamosain gathered alone into a single branch. Quantitative real-time PCR exhibited that the relatively abundant expression of elovl6b was observed in intestine and stomach, and the elovl6a and elovl6c were highly expressed in hepatopancreas. In addition, studies found that replacing fish oil with soybean oil could significantly increase the transcriptional levels of three elovl6 in hepatopancreas of S. paramamosain, and the expression of elovl6a and elovl6c in hepatopancreas were more sensitive to dietary fatty acids than the elovl6b. Compared with the normal sea water group (27‰), the expression of sterol-regulatory element binding protein1c (srebp-1), elovl6a, elovl6b and elovl6c were upregulated in the low salinity groups, particularly in 7‰. On the contrary, the starvation stress suppressed the expression of srebp-1, elovl6a, elovl6b and elovl6c. Discussion: These results may contribute to understand the functions of elovl6 in fatty acid synthesis and regulatory mechanisms in crustaceans.